Public opinion analysis for moderate religious: Social media data mining approach - Mudhofi, M.; Supena, Ilyas; Karim, Abdul; Safrodin, Safrodin; Solahuddin, Solahuddin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose - This paper aims to elaborate discourses of religious moderation on social media in terms of perceptions of netizen’s responding to the values of religious moderation.Method - This study uses text mining to interpret and categorize comments from Twitter about the values of moderation. In addition, sentiment analysis used to capture the number of positive and negative words in each tweet. Data analysis was used to extract and explore the dominant Twitter users' emotions around the values of moderation.Result - Sentiment analysis results indicate the variance of Twitter users' public participation in providing perceptions of religious or religious moderation values. The variance of public views of Twitter users on the issue of religious moderation content shows that positive sentiment is higher than negative sentiment.Implication – This research contributes to the study of religious moderation more broadly by understanding how social media users perceive and showing how machine learning (text mining) can help better understand concepts related to the values of moderation.Originality - This study presents a new methodology and analytical approach to investigating moderate religious in social media conversations, which brings together a multidisciplinary knowledge of technology, data science and religious studies. This research is the first study that used data mining approach to public opinion analysis for moderate religious in Indonesia.***Tujuan - Tulisan ini bertujuan untuk mengelaborasi wacana moderasi beragama di media sosial ditinjau dari persepsi warganet dalam menyikapi nilai-nilai moderasi beragama.Metode - Penelitian ini menggunakan text mining untuk menginterpretasikan dan mengkategorikan komentar dari Twitter tentang nilai moderasi. Selain itu, analisis sentimen digunakan untuk menangkap jumlah kata positif dan negatif di setiap tweet. Analisis data digunakan untuk mengekstraksi dan mengeksplorasi emosi pengguna Twitter yang dominan seputar nilai moderasi.Hasil - Hasil analisis sentimen menunjukkan adanya variansi partisipasi masyarakat pengguna Twitter dalam memberikan persepsi terhadap agama atau nilai moderasi beragama. Variasi pandangan masyarakat pengguna Twitter terhadap isu konten moderasi beragama menunjukkan bahwa sentimen positif lebih tinggi daripada sentimen negatif.Implikasi – Penelitian ini berkontribusi pada kajian moderasi beragama secara lebih luas dengan memahami bagaimana persepsi pengguna media sosial dan menunjukkan bagaimana machine learning (text mining) dapat membantu lebih memahami konsep yang berkaitan dengan nilai-nilai moderasi.Orisinalitas - Studi ini menyajikan metodologi baru dan pendekatan analitis untuk menyelidiki agama moderat dalam percakapan media sosial, yang menyatukan pengetahuan multidisiplin teknologi, ilmu data, dan studi agama. Penelitian ini merupakan penelitian pertama yang menggunakan pendekatan data mining untuk analisis opini publik terhadap agama moderat di Indonesia.